Association Between Endovascular Therapy Time to Treatment and Outcomes in Patients With Basilar Artery Occlusion. Issue 12 (22nd March 2022) - Joundi, Raed A.; Sun, Jie-Lena; Xian, Ying; Alhanti, Brooke; Nogueira, Raul G.; Bhatt, Deepak L.; Fonarow, Gregg C.; Saver, Jeffrey; Schwamm, Lee H.; Smith, Eric E.
Abstract : Background: Basilar artery occlusion (BAO) is a devastating condition without definitive evidence to guide treatment. Whereas the association between faster treatment times with endovascular therapy (EVT) and better outcomes in anterior circulation is well established, whether this relationship exists for patients with BAO is not well delineated. Methods: We used individual-level patient data from the Get With The Guidelines–Stroke nationwide US registry prospectively collected from January 2015 to December 2019. We identified individuals with BAO treated with EVT within 24 hours of symptom onset. The primary outcomes examined were in-hospital mortality, discharge home, ambulatory at discharge, independent at discharge (modified Rankin Scale score 0 to 2), substantial reperfusion (modified Thrombolysis in Cerebral Infarction score 2b or 3), and symptomatic intracranial hemorrhage. Using logistic regression models, we evaluated the association between time from symptom onset to treatment with EVT and outcomes. Results: Among 3015 patients with BAO treated with EVT, the mean age was 65.9 years, 38.8% were women, and the median National Institutes of Health Stroke Scale score at presentation was 17 (interquartile range, 8–26). Median onset to EVT time was 406 minutes (interquartile range, 252–688). From 2015 to 2019, there was an overall increase in the median onset to EVT times (380–411 minutes; P =0.016) but no significant change in the proportion of patients treated within 6 hours of symptom onset (48.4%–44.0%; P =0.17). After risk adjustment for patient and hospital-level factors, there were significantly lower odds of in-hospital mortality (adjusted odds ratio [aOR], 0.55 [95% CI, 0.45–0.68]) and symptomatic intracranial hemorrhage (aOR, 0.52 [95% CI, 0.32–0.84]) and significantly higher odds of ambulation at discharge (aOR, 1.72 [95% CI, 1.37–2.16]), discharge home (aOR, 2.19 [95% CI, 1.73–2.77]), and independence at discharge (aOR, 2.21 [95% CI, 1.66–2.95]) when onset to EVT time was ⩽6 hours compared with >6 hours. The fastest decay in good outcomes per hour occurred within 6 hours of symptom onset. Conclusions: Among patients receiving EVT for BAO, faster treatment from symptom onset was associated with improved outcomes. These findings support efforts to achieve rapid treatment with EVT for patients with BAO.